Transvaginal ultrasound during pregnancy: perception and acceptability of antenatal clinic attendees at the University College Hospital, Ibadan. (2017)
Introduction: There has been a tremendous increase in the use of transvaginal ultrasound (TVS) in pregnancy. With the use of high resolution transducers, the transvaginal probe has proved to be particularly useful for finding the location and dating of early pregnancies when compared with transabdominal sonography (TAS). It has also been shown to be a reliable method for confirming complete miscarriage. This study aims at determining the perception and acceptability of TVS in pregnancy. Materials and Methods: This is a descriptive cross sectional study of 424 consenting pregnant women attending the antenatal clinic at the University College Hospital, Ibadan. Using a self administered questionnaire, we obtained information on their socio demographic characteristics, awareness of ultrasound and TVS and opinion about TVS including acceptability and perceived complications. Results: The mean age of the respondents was 31.6 ± 4.7 years. Majority (410; 96.7%) had heard about ultrasound scanning, and 395 (93.2%) had undergone at least one type. Approximately two fifth (177; 41.7%) had heard about TVS, mostly from antenatal clinic, with two third having a good knowledge. Only 90 (21.2%) had personal experiences, and 144 (34%) believed it is harmful; however, about three fifths (256; 60.4%) were willing to do TVS if indicated. Perceived complications of TVS included abortion, infection and bleeding. Awareness and perception were strongly associated with acceptability of TVS but not with education or previous experience. Conclusion: This study shows that the perception and acceptability of TVS by pregnant women is dependent on their level of awareness. There is an urgent need for proper information dissemination on the usefulness, safety and advantages of TVS in pregnancy.